A Comparative Analysis of the Interpretations of the Shia and Sunni Regarding Mahramiyat by Breastfeeding based on Verse 23 of Surah Nisa - ali farsimadan (پژوهش نامه معارف قرآنی, 2023)
one of the ways to become Mahram is breastfeeding (Shir-Dadan). The present study aims to answer this main question with a descriptive and analytical method: Does the noble verse imply the amount of breastfeeding in proving the Mahramiyat in the Shia and Sunni interpretations? The author has tried to study this issue from the perspective of Imamiyyah interpretations and Sunni interpretations. The interpretations and jurisprudence of the Imamiyyah have discussed Mahramiyat by breastfeeding from three aspects of effect, number, and time, but the interpretations and jurisprudence of Ahl al-Sunnah have given two aspects of effect and number. The common denominator of both is the effect that is effective in creating Mahramiyat by breastfeeding. From the application of the verse, it is not possible to give a rule on the amount of milk in becoming Mahram by breastfeeding, and to understand the rule, one must refer to the sayings and arguments of the jurists. Imami commentators have mentioned various sayings such as 1 time, 10 times, 15 times and 15 days and nights among which they have strengthened the number 15 times because it is close to "effect" and other sayings have problems. Sunni commentators have not mentioned a specific number and amount, but Sunni commentators and jurists have stated sayings such as: mere breastfeeding, 3 times, 4 times, 5 times, and 10 times, and there is no firm word or indicator here. It is an important point that the researches in Shia and Sunni interpretations indicate that their arguments in applying the noble verse and specifying the amount of milk in the Mahramiyat by breastfeeding are incomplete, and to prove the Mahramiyat by breastfeeding, one should refer to the traditions and legal books of different parties